Evidence of laser-induced nanobubble formation mechanism in water - Miha Jelenčič; Uroš Orthaber; Jaka Mur; Jaka Petelin; Rok Petkovšek (Ultrasonics Sonochemistry, 2023)
Principles of laser-induced nanobubble formation in water are studied and presented. Nanobubbles were generated by laser light at intensities below threshold for laser-induced breakdown and subsequently expanded by a rarefaction wave to facilitate their observation and analysis. Different methods were used to study nanobubble formation and characteristics. Firstly, probability of nanobubble formation as a function of water sample purity was examined. Secondly, relation between laser fluence at different wavelengths and the number of generated nanobubbles was investigated. Thirdly, measurements of nanobubble lifetime were conducted indicating a contradiction to the Epstein-Plesset equation-based prediction of free bubble dissociation. Accumulated evidence suggests that the presence of physical impurities is a prerequisite for nanobubble formation. Consequently, a lack of impurities results in the absence of nanobubbles in contrast to assumptions by existing studies. The findings presented in this paper provide new insights into the fundamental properties of laser-induced nanobubbles in water.